EDUCATION WITH TECHNOLOGIES AND POLITICAL-PEDAGOGICAL PROJECT - Porfírio, Luciana Cristina; Lopes, Rosemara Perpétua [UNESP] (My University, 2022)
This article reports the results of a study aimed at investigating the relationship between the political-pedagogical projects of public schools in Goiás and the Special Regime for Non-Current Classes (REANP) during the Covid-19 social distancing period. Supported by the concepts of regulatory and emancipatory innovation, among others, we conducted documentary research that covered 19 documents dated 2020. The results point to evidence of emancipatory innovation and also of regulatory innovation, with a predominance of the latter, evidenced by the prescriptive and imposing nature of the contents and planned actions. The technological resources mentioned in these documents were WhatsApp, Facebook, Google Meet and email. Although dated 2020, not all of the projects analyzed mentioned REANP.
EDUCAÇÃO COM TECNOLOGIAS E PROJETO POLÍTICO-PEDAGÓGICO
Keywords: Digital; Education; Political-pedagogical project; Teaching work